Jornalismo e boataria no caso Marielle vozes e sentidos na notícia combustível de fake news - Silva, Andréa Maria Batista da (2020)
We analyzed the journalistic treatment given to false rumors against the city councilwoman, Marielle Franco (Psol-RJ), in March 2018. The rumors were born in WhatsApp groups, were validated on Facebook by a representative of the Brazilian justice system and gained notoriety through a news, considered “fuel” for fake news, published by Folha de S. Paulo and replicated by other media outlets, including Veja's websites Veja magazine and Extra newspaper, the blog Ceticismo Político and the paraibano Portal T5. In the form of journalism, the slander against the parliamentarian returned to social media and was shared at least 650 thousand times, in just over 48 hours. From this case and, specifically, from the analysis of the journalistic coverage given to the fact, we identify the voices and the senses moved in the speeches. We question the extent to which the rigor in checking the facts and sources and the use of polyphony in the construction of a text can prevent professional journalists from becoming rumors. In the five analyzed articles, we see class struggle, ideology in discursive formations and silencing. Given the alleged objectivity of journalism, we seek the contribution of French Discourse Analysis (AD) to understand that although the technique differentiates a professional journalist from a content producing citizen and is essential for reporting events, texts can always be re-signified by the recipients. As Orlandi (2007) warns, we are condemned to interpret.